STUDI DESKRIPTIF PENDIRIAN USAHA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS SRIWIJAYA - Deskoni; Yuliana FH; Firmansyah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2021)
This research aims to find out what business is being pursued by students and describe how the process of establishing the business was conducted by students of the year 2018-2020 of the Economic Education Study Program of Sriwijaya University. The research method used is descriptive qualitative research, by conducting observations and in-depth interviews of informants/ respondents of 20 entrepreneurship students to obtain the required data following the focus of the research. In starting a business most students have had an entrepreneurship intention since high school / vocational school, the determination was stronger with the support of several courses such as entrepreneurship, business planning, and UMKM. The motivation of students to start a business is largely influenced by the desire to be independent (ambition for freedom), and in choosing a business that is run based on hobbies and skills owned and taking advantage of existing business opportunities. However, in starting a business most students did not make a mature business plan, even though business planning can be said to be a tool of control in achieving business focus and goals.